2020
DOI: 10.21608/ebwhj.2020.27971.1087
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Use of Autologous Platelet-Rich Plasma in Management of Asherman Syndrome: A Randomized Controlled Trial

Abstract: Background: Operative hysteroscopy with lysis of intrauterine adhesions is a viable treatment option for Asherman syndrome. However, with all forms of adhesion resection, there is a high rate of reformation of intrauterine adhesions. The current study will focus on a unique technique to evaluate the use of platelet rich plasma over an inflated balloon versus conventional method (inflated balloon). Aim: This study aim to assess the efficacy of the platelet rich plasma in preventing reformation of intrauterine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…Of the six RCT studies (13,(18)(19)(20)(21)25), those with appropriate randomization methods had a low risk of process bias in randomization. One study (18) had a high risk of bias for deviations from the intended interventions because the patients knew which intervention they received during the trial.…”
Section: Risk Of Bias Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the six RCT studies (13,(18)(19)(20)(21)25), those with appropriate randomization methods had a low risk of process bias in randomization. One study (18) had a high risk of bias for deviations from the intended interventions because the patients knew which intervention they received during the trial.…”
Section: Risk Of Bias Of Included Studiesmentioning
confidence: 99%
“…The effects of platelet-rich plasma (PRP) on changes in menstrual flow and duration were reported in three trials (19)(20)(21) involving a total of 259 participants. The results indicated that PRP administration led to an increase in menstrual flow (WMD = 2.96, 95% CI = 2.30-3.61; P < 0.001; I 2 = 0.0%) and days of menstruation (WMD = 1.13, 95% CI = 0.86-1.41; P < 0.001; I 2 = 0.0%) (Figure 3).…”
Section: Menstruation Flow and Durationmentioning
confidence: 99%
“…El manejo actual del síndrome de Asherman se enfoca en eliminar las adherencias, prevenir la recurrencia y proporcionar factores estimulantes locales para regenerar el tejido sano (Naghshineh et al, 2023) (Lusine Aghajanova et al, 2021). La lisis histeroscópica de las adherencias ha sido el tratamiento realizado por años, sin embargo, ha demostrado altas tasas de recidiva (3,1% y 23,5%,) sobre todo en adherencias graves que requieren sesiones repetidas en intervalos cortos de tiempo (Sameh et al, 2020). Las terapias actuales son variadas, algunas emplean estrógenos exógenos, vitamina E, L-arginina, citrato de sildenafilo vía vaginal, pentoxifilina y aspirina, todas ellas con éxito limitado.…”
Section: Introductionunclassified
“…Se utiliza desde 1980, después de un proceso de extracción y centrifugación de la sangre total, obteniendo un concentrado de 1.000.000 plaquetas por microlitro (Dreisler & Kjer, 2019b). El PRP tiene un gran potencial regenerativo de los tejidos, ya que favorece la angiogénesis, migración, diferenciación y proliferación celular debido a su alto contenido en factores de crecimiento como factor de crecimiento endotelial vascular (VEGF), factor de crecimiento epidérmico (EGF), factor de crecimiento derivado de plaquetas (PDGF), factor de crecimiento transformante (TGF) y citocinas (Sameh et al, 2020) (Sharara et al, 2021). A diferencia de otros tratamientos regenerativos, la infusión de PRP es una técnica segura, asequible y menos invasiva en pacientes con endometrio alterado (Dreisler & Kjer, 2019b).…”
Section: Introductionunclassified